Lessons from Utopia. Issue 2 (1st June 2017) - Duncombe, Stephen; Lambert, Steve
Over the past decade the Center for Artistic Activism has trained over 1000 activists and artists from around the world how to be more creative in their activist work and strategic in their artistic practice. Central to this training is the concept of Utopia. This article explains how Thomas More's Utopia was designed not as a plan of an ideal society, but as a prompt to stimulate the reader's own political imagination. It is argued that Utopia is essential for social movements, and can be used to demonstrate another world could be possible, as a means to critique the present society, as a method to generate new models of society, as a tool to orient movement towards a goal, and as a way to motivate others into joining the struggle for social change. The liabilities of the artistic activist use of dystopia are also discussed.